Civil War Branding For Global Economy Stability? (Propaganda Review on Russian – Ukrainan War) - Fardila, Ucik Ana (CV. ULIL ALBAB CORP, 2025)
McCombs and Shaw's political agenda theory explains Civil War Branding by claiming that concerns in the media and public are part of the authorities' agenda-setting. The paper investigates the branding of civil wars in the global political economy agenda. The study has looked at numerous viewpoints and sciences, but as it nears its conclusion, it will focus on the concept of agenda-setting from the standpoint of political communication science. The study employs Brian McNair's idea on the government's use of the concept of the enemy to influence public opinion in order to persuade people to support the government's agenda against the enemy. Data was gathered by conducting an analysis on https://search.mediacloud.org/ using the keywords civil war Russia Ukraine. Data was gathered by conducting an analysis on https://search.mediacloud.org/ using the keywords civil war Russia Ukraine. The data covers the period from January 12, 2022 to December 31, 2023. The results show that the Russia-Ukraine war peaked in March and July 2023, with the majority of news accessible from yahoo.com, and the most commonly used language is English (91%), followed by French (3%), and Danish (2%). The study's findings reveal that the media has control over giving information about the conflict; any policy changes that occurred throughout the war were reported as a reference, which had an impact not only on the state system's policies, but also on the economy.